Exploring the potential of myo-inositol in thyroid disease management: focus on thyroid cancer diagnosis and therapy - Razavi, S. Adeleh; Kalari, Mohadeseh; Haghzad, Tahereh; Haddadi, Fatemeh; Nasiri, Shirzad; Hedayati, Mehdi (Frontiers in Endocrinology, 2024)
Thyroid cancer (TC) is a malignancy that is increasing in prevalence on a global scale, necessitating the development of innovative approaches for both diagnosis and treatment. Myoinositol (MI) plays a crucial role in a wide range of physiological and pathological functions within the human cell. To date, research has been conducted to investigate the function of MI in thyroid physiology as well as its potential therapeutic benefits for hypothyroidism and autoimmune thyroiditis. Metabolomics studies have highlighted the promising diagnostic capabilities of MI, with it being recognized as a metabolic biomarker for the identification of thyroid tumors. Furthermore, MI possesses the capability to influence therapeutic characteristics by modulating key cellular pathways that are involved in TC. This review provides an evaluation of the potential application of MI as a naturally occurring compound in the management of thyroid diseases including hypothyroidism, autoimmune thyroiditis, and especially TC. The limited number of studies conducted in this field emphasizes the crucial requirement for future studies to comprehend the multifaceted role of MI in TC. A significant amount of research and clinical trials are necessary to understand the role of MI in the pathology of TC, its diagnostic and therapeutic potential, and to open the path for personalized medicine strategies in managing this intricate disease.